GIS approach to quantifying variable risk and vulnerability to hazards posed by volcanoes in remote regions: a case study for the region of Santiago Atitlán, Guatemala - Shayler, Holly (The University of Edinburgh, 2022)
This dissertation examines the need to consider varying risk of communities to hazards from the Atitlán volcano, Guatemala, on both a spatial and temporal scale by creating a risk score for the populated areas based on their locations during the day and the night. This score was devised through a multi-criteria evaluation which combines multiple variables from the categories social, territorial, and physical, to create an overall score. The variables themselves were calculated using GIS to both analyse current data and to interpolate values where data was missing. The results show that during the day the population is both more widely dispersed and that there are more groups closer to the volcanic crater and so at a higher risk. The results also indicate that the communities of Panabaj and Tzanchaj are at the highest risk, with variations throughout the rest of the region outlining the usefulness of an MCE over a purely situational analysis. This project also demonstrates how GIS can be used both to calculate these variables and to create the risk score, outlining its effectiveness in interpolating values where needed and visualising the results for effective evacuation planning and awareness of at-risk communities.
A GIS approach to quantifying variable risk and vulnerability to hazards posed by volcanoes in remote regions: a case study for the region of Santiago Atitlán, Guatemala
Keywords: Risk Assessment; Volcanic Hazards; Vulnerability; Geographical Information Systems